The impact of timing in written corrective feedback on collaborative writing and L2 accuracy development - Michaud, Gabriel; McDonough, Kim; Parent, Mariane (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2025)
This study examines the impact of written corrective feedback (WCF) timing on the collaborative writing process and writing accuracy development of adult learners of French as a second language. Forty-eight learners were divided into three groups to complete a collaborative writing task in pairs. The first group received immediate WCF via Google Docs while writing, the second group received delayed WCF one week later with 10 minutes allocated for error correction, and the third group performed the writing task without receiving any feedback. All discussions during the collaborative writing were recorded and analyzed for language-related episodes (LREs). Writing accuracy was assessed through pretests, immediate posttests, and delayed posttests using story-retelling tasks. The findings revealed that the delayed feedback group engaged in more extensive discussions about linguistic forms compared to the other two groups. In terms of writing accuracy, the immediate feedback group showed the most significant improvements over time.